EVALUASI LEVEL PENGUNGKAPAN ISLAMIC SOCIAL RESPONSIBILITY PERBANKAN SYARIAH DI INDONESIA - Khadijah Ath Thahirah; Rahmaita Rahmaita (Universitas Negeri Surabaya, 2018)
This study aims to evaluate and analyze the Islamic Social Responsibility Disclosures level of Islamic Bank in Indonesia using a disclosure index approach that was developed by Maali et al (2003).The analyzing was developed from 32 disclosure items that must Islamic Bank disclose in their annual report for every year. The level of Islamic social responsibility disclosure varies significantly across the sample. The checklist item result suggest that level of Islamic Social Responsibility Disclosure of Islamic Banking in Indonesia need more attention from the expert of Islamic Accounting, The Standar Accounting Board and Islamic Bank